2020
DOI: 10.1109/access.2020.3011137
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Certification Towards Distributed Authentication Infrastructure: A Case of Hyperledger Fabric

Abstract: In Internet of Things ecosystems, where various entities trade data and data analysis results, public key infrastructure plays an important role in establishing trust relationships between these entities to specify who trusts whose private keys. The owner of a private key is provided with a public key certificate issued by a certificate authority (CA) representing a trusted third party. Although this certificate ensures the reliability of the ecosystem by verifying the data source and preventing the denial of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…An attacker can exploit a homograph attack by confusing a server in distinguishing the name of an original certificate from the name of a fake one [56]. Session key exposure is distributing a fake key to the target network to mislead victims and take data stealthily from them.…”
Section: Discussionmentioning
confidence: 99%
“…An attacker can exploit a homograph attack by confusing a server in distinguishing the name of an original certificate from the name of a fake one [56]. Session key exposure is distributing a fake key to the target network to mislead victims and take data stealthily from them.…”
Section: Discussionmentioning
confidence: 99%
“…The authorization efficiency is improved while ensuring the security of distributed authorization, but the first strategy requires higher computational cost. To solve the problem of centralized CA authentication, Kakei [38] proposed a strategy for distributed CA authentication (Fabric). In Figure 15, it is shown that the CA nodes in Texas are divided into meta-CA and CA.…”
Section: Iot Securitymentioning
confidence: 99%
“…To classify the reviewed proposals, we have divided them according to their implementation, as follows: a: Classical PKI Systems improved with blockchain This classification shows pseudo-decentralised implementation where traditional CAs are the main part of the implementation to generate the PKI system, besides the use of blockchain. For example, Kakei et al [38] present crosscertification system for CAs on a PKI based on Hyperledger blockchain. This proposal uses three layers for PKI: 1) users, where all CA existent users are registered, 2) CAs, where all the classic CAs communicate with each other, and 3) the ledger, consisting of entities known as meta-CAs, which functions as the Hyperledger nodes.…”
Section: ) Practical Developmentsmentioning
confidence: 99%